Cerebrospinal Fluid Pseudocyst Complicating Ventriculoperitoneal Shunt: Report of Four Cases - Pan, Pradyumna (Indian Journal of Neurosurgery, 2018)
Background Cerebrospinal fluid (CSF) abdominal pseudocyst (APC) is an uncommon complication following ventriculoperitoneal (VP) shunt.Aim To study the clinical features and management of this entity. The authors present their experience with cases of CSF pseudocyst in children.Materials and Methods Retrospective analysis of four cases diagnosed to have APC following VP shunt between 2005 and 2015.Results Clinical presentation was with progressive abdominal distension, highlights of intestinal obstruction, and signs of raised intracranial pressure (ICP). Diagnosis is readily made with ultrasonography and computed tomographic (CT) scan of the abdomen. The duration between insertion of the shunt and the presentation ranged from 4.11 to 12 years. In three patients, the cyst was unilocular and of varying size. The fourth one had a multilocular cyst. In three patients, the treatment involved was surgical removal of the catheter with excision of the pseudocyst wall and placement of a new catheter intraperitoneally in a different quadrant. Ultrasound-guided aspiration of the cyst and relocation of the distal end was done in one patient.Conclusion Initial suspicion with appropriate investigation and early treatment can avert morbidity and mortality.
Keywords: cerebrospinal fluid abdominal pseudocyst; ventriculoperitoneal shunt complication; management